2009
DOI: 10.1253/circj.cj-09-0057
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin and Cardiovascular Disease

Abstract: Obesity is strongly associated with metabolic and cardiovascular disorders. Adiponectin is an adipose-derived plasma protein that is downregulated in subjects with obesity-related disorders. Low levels of adiponectin are associated with the increased prevalence of obesity-linked cardiovascular diseases, including ischemic heart disease and peripheral artery disease. Experimental findings have shown that adiponectin has beneficial effects in the cardiovascular system by directly acting on the component cells of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
145
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 194 publications
(155 citation statements)
references
References 101 publications
(121 reference statements)
6
145
0
4
Order By: Relevance
“…Adiponectin is an adipocytokine that is exclusively produced by adipocytes (6,7). Plasma adiponectin levels are decreased in obese subjects (10), and adiponectin is down-regulated in association with obesity-linked disorders including type 2 diabetes, hypertension, atherosclerosis, and ischemic heart disease (6,7).…”
Section: Doxorubicin (Dox)mentioning
confidence: 99%
See 1 more Smart Citation
“…Adiponectin is an adipocytokine that is exclusively produced by adipocytes (6,7). Plasma adiponectin levels are decreased in obese subjects (10), and adiponectin is down-regulated in association with obesity-linked disorders including type 2 diabetes, hypertension, atherosclerosis, and ischemic heart disease (6,7).…”
Section: Doxorubicin (Dox)mentioning
confidence: 99%
“…Plasma adiponectin levels are decreased in obese subjects (10), and adiponectin is down-regulated in association with obesity-linked disorders including type 2 diabetes, hypertension, atherosclerosis, and ischemic heart disease (6,7). Consistent with these clinical observations, experimental studies demonstrate that adiponectin deficiency contributes to exacerbation of insulin resistance, hypertension, vascular dysfunction, and cardiac remodeling under conditions of stress (11)(12)(13), indicating the protective actions of adiponectin on various obesity-inducible complications.…”
Section: Doxorubicin (Dox)mentioning
confidence: 99%
“…28- 31 The use of a formula food has been reported to increase the level of adiponectin. 32 Figure 3 shows the Table 4) and adiponectin (μg/ml), from baseline to 20 weeks (baseline value minus that at 20 weeks).…”
Section: Formula Food With Soy Protein Vs Milk Proteinmentioning
confidence: 99%
“…Okamoto et al (39) demonstrated that adiponectin levels are negatively associated with BMI and fat content. The mechanisms implicated in the regulation of adiponectin remain unknown, but exercise increases adiponectin levels (16,40), as shown here. Furthermore, we found that lean mass is higher in BDs, and that there is a positive correlation between adiponectin levels and lean mass.…”
Section: Discussionmentioning
confidence: 60%
“…This peptide acts as a satiety signal that stimulates energy expenditure regulating body weight (11), with these actions being modulated by a soluble receptor (12). Physical exercise increases adiponectin levels (13) and the expression of its receptors in muscle (14), and this adipokine may have beneficial effects on the cardiovascular system (15,16).…”
Section: Introductionmentioning
confidence: 99%